The use of bone scintigraphy to detect active Hansen's disease in mutilated patients - Braga, FJHN; Foss, N. T.; Ferriolli, E.; Pagnano, C.; Miranda, JRD; de Moraes, R. (Springer, 1999)
Mutilation of extremities was very frequent in patients affected by leprosy in the past; although it is now much less common, it is still seen, mainly in patients with long-term disease. In general, mutilation of the nose and ears is caused by the bacillus and mutilation of the hands and feet a consequence of chronic trauma. Leprosy must be chronically treated and any decision to interrupt therapy is based on laboratory tests and biopsy. Scintigraphy is a non-invasive procedure which could be of great value in to determining disease activity. We studied eight patients (five males and three females, aged 64-73 years) who presented with mutilation of the nose (2), ear (1), feet (3) or foot and hand (2), Conventional three-phase bone scintigraphy (750 MBq) and X-ray examinations of the affected areas were performed in all patients. Bone scintigraphy was abnormal in four patients (the presence of bacilli was confirmed by biopsy in two of them), and normal in the other four. In all patients except for the one with ear mutilation, radiography only showed the absence of bone. We conclude that bone scintigraphy is very useful to determine disease activity in cases of mutilation caused by leprosy. It seems to be superior to conventional radiography and may enable bone biopsies to be avoided.
Keywords: leprosy; Hansen's disease; scintigraphy; mutilation; technetium-99m methylene diphosphonate